Productivity changes in the Mediterranean Sea for the twenty-first century in response to changes in the regional atmospheric forcing - Macias, Diego M.; Garcia-Gorriz, Elisa; Stips, Adolf (Frontiers in Marine Science, 2015)
The Mediterranean Sea is considered as a hotspot for climate change because of its location in the temperate region and because it is a semi-enclosed basin surrounded by highly populated and developed countries. Some expected changes include an increase in air temperature and changes in the periodicity and spatial distribution of rainfall. Alongside, demographic and politics changes will alter freshwater quantity and quality. All these changes will have an impact on the ecological status of marine ecosystems in the basin. We use a 3D hydrodynamic-biogeochemical coupled model of the entire Mediterranean Sea to explore potential changes in primary productivity (mean values and spatial distribution) under two emission scenarios (rcp4.5 and rcp8.5).To isolate the effects of changes in atmospheric conditions alone, in this ensemble of simulations rivers conditions (water flow and nutrient concentrations) are kept unchanged and equal to its climatological values for the last 10 years. Despite the significant warming trend, the mean integrated primary production rate in the entire basin remains almost unchanged. However characteristic spatial differences are consistently found in the different simulations. The western basin becomes more oligotrophic associated to a surface density decrease (increase stratification) because of the influence of the Atlantic waters which prevents surface salinity to increase. In the eastern basin, on the contrary, all model runs simulates an increase in surface production linked to a density increase (less stratification) because of the increasing evaporation rate. The simulations presented here demonstrate the basic response patterns of the Mediterranean Sea ecosystem to changing climatological conditions. Although unlikely, they could be considered as a ‘baseline’ of expected consequences of climatic changes on marine conditions in the Mediterranean.